ANALISIS PENGARUH KUALITAS DAN MEREK TERHADAP MINAT BELI KONSUMEN PADA PT. TAPANULI MOTOR SIBOLGA - Tarigan, Nova Sugana (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
Abstract The purpose of this study is to determine and analyze the effect of quality and brand on consumer buying interest at PT. Tapanuli Motor Sibolga. Provisional answers (Hypothesis) for this research are: There is a joint effect of quality and brand on consumer buying interest at PT. Tapanuli Motor Sibolga. The population in this study are consumers who make motorcycle purchases at PT. Tapanuli Motor Sibolga during the month of October 2017 as many as 30 people and used as samples. The data analysis technique used is multiple linear regression analysis. Based on the research results, it is known that the R Square determination coefficient of 0.616 means that 61.6% of buying interest can be influenced by quality (X1) and brand (X2). While the simultaneous test results obtained Fcount (21,671) is greater than Ftable (3.32) or (21,671> 3.32) means that quality and brand simultaneously affect the consumer buying interest at PT. Tapanuli Motor Sibolga. The partial test results known t-test value of 2.966> t-table value of 2.042 (2.966> 2.042) or significant (Sig-t) of 0.006 <Î± (0.05) means that partially the quality variable has a positive and significant effect on interest buy consumers at PT. Tapanuli Motor Sibolga. Partial test results known t-count value of 3.462> t table value of 2.042 (3.462> 2.042) or significant (Sig-t) of 0.000 <Î± (0.05) means that partially brand variables have a positive and significant effect on interest buy consumers at PT. Tapanuli Motor Sibolga. The multiple linear regression model in this study is Y = 10.494 + 0.332 X1 + 0.488 X2 the influence of quality and brand on consumer buying interest at PT. Tapanuli Motor Sibolga shows a positive direction. Suggested PT. Tapanuli Motor Sibolga can maintain the quality and brand of products offered to consumers, in order to maintain the motorcycle market segment in Sibolga and Central Tapanuli Regency.